Goal disturbance changes pre/post‐renal transplantation are related to changes in distress. Issue 3 (22nd May 2017) - de Vries, Alicia M.; Schulz, Torben; Westerhuis, Ralf; Navis, Gerjan J.; Niesing, Jan; Ranchor, Adelita V.; Schroevers, Maya J.
Abstract : Objective: Renal transplantation (RTx) is considered the treatment of choice for end‐stage renal disease (ESRD) given its association with lower mortality, and improved overall quality of life and psychological functioning compared to dialysis. However, much less is known about which factors underlie these psychological improvements across RTx. Goal theory suggests that experienced disturbances in important goals are related to lower psychological functioning. This study aimed to (1) identify the most disturbed and most important goals for patients before RTx, (2) to examine changes in goal disturbance and goal importance pre/post‐RTx, and (3) to examine whether changes in goal disturbance are associated with changes in psychological distress over time, and whether this relationship is mediated by changes in perceived control. Methods: In this longitudinal study, 220 patients completed questionnaires before and after RTx, including questionnaires to assess goals (GOALS questionnaire), psychological distress (GHQ‐12), and perceived control (Mastery scale). Results: End‐stage renal disease affected both general and disease‐specific goals. Approximately 30% of the patients indicated to experience high or very high disturbance before transplantation. Goal disturbance generally decreased significantly pre‐ to post‐RTx, whereas goal importance did not change significantly pre‐ to post‐RTx. No mediation effect of perceived control was found. Instead, both changes in goal disturbance and perceived control showed independent effects on changes in distress. Conclusions: Intervention strategies targeting attainable and realistic goal setting, and perceived control in RTx recipients who do not benefit optimally from RTx, might enhance psychological functioning in this population. Statement of contribution What is already known on this subject? Kidney transplantation improves patients' psychological functioning. Experienced disturbances in important life goals are related to lower psychological functioning in chronic illness. What does this study add? Goal disturbance decreases after renal transplantation, and this is related to a decrease in distress over time. Perceived control does not mediate the relationship between goal disturbance and distress pre/post‐transplantation. Changes in perceived control have an additional main effect on changes in distress.